Impacts of Reproductive Technologies on Beef Production in South America - Vasconcelos, José Luiz Moraes [UNESP]; Sa Filho, Ocilon Gomes de [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Lamb, G. C.; DiLorenzo, N. (Springer, 2014)
The majority of beef cow herds in South America are constituted by Bos indicus females, which have particular reproductive features that contribute to reduced reproductive efficiency compared with that of B. taurus cohorts. Hence, several alternatives to enhance reproductive efficiency of B. indicus heifers and cows have been developed to address their inherent reproductive shortcomings. These research-based technologies are being described in detail within this chapter and have already made an impact on South American B. indicus-based production systems. These include the following: (a) hormonal protocols to induce puberty in nulliparous heifers or estrous cyclicity in postpartum cows to maximize their reproductive performance during the subsequent breeding season, (b) hormonal protocols to synchronize estrus and/or ovulation in B. indicus females to exploit their reproductive responses to artificial insemination, and (c) genetic and environmental factors that influence reproductive success in beef herds, including reproductive diseases and excitable temperament of B. indicus females, that have been investigated to support/promote the development of appropriate mitigation technologies.
Keywords: Artificial insemination; Bos indicus; Beef females; Estrus synchronization; Reproduction; South America